A numerical study of bipolar charging and neutralization of ultrafine particles with uniformly generated heterogeneous ions. (November 2020) - Carsí, M.; Alonso, M.
Abstract: Bipolar charging and neutralization of aerosol particles below 100 nm in a laminar flow tube with a uniform generation rate of mass- and mobility-distributed heterogeneous ions has been studied theoretically, and compared to the case of homogeneous, monodisperse ions. Two types of homogeneous ions have been examined: type-I, having the arithmetic mean mass and mobility of the heterogeneous ions; and type-II, having the same mean mobility but with a mass chosen so as to yield the same mean ion-to-aerosol attachment rate coefficients as the heterogeneous ions. By definition, heterogeneous and homogeneous-II ions lead to the same stationary charge distribution, but homogeneous-I ions lead to a different one. If the bipolar charger operates under non-stationary conditions, each ion type produces a different aerosol charge distribution. Using five different sets of bipolar heterogeneous ion populations, with mobility (and in some cases, mass) distributions measured by different research groups, it has been found that the two types of homogeneous ions, I and II, reproduce with reasonable accuracy the charge distributions yielded by the heterogeneous ions, except for multiply-charged particles in a few specific cases. For the particular charger studied, the stationary charge distribution is attained, within a ±5% error, when the dimensionless number β N i n 2 τ / n i n introduced in Ibarra, Rodríguez-Maroto, and Alonso (2020) is larger than about 2000. Other charger geometries may lead to a different threshold value for this dimensionless number. Highlights: Stationary charge distribution (SCD) depends on the type of heterogeneous ions. But it can be fairly well predicted by ionic mean mass and mobility. Spatially uniform ion generation gives a definite SCD. Non-uniform ion generation profile should affect the SCD. A dimensionless number is proposed to check stationarity.